Challenges of Female Entrepreneurship Pre-, During- and Post-Covid-19 Prospects in South Africa - Chux Gervase Iwu; Lucky Sibanda; Tendai Makwara (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Female entrepreneurship discourse continues to receive heightened attention owing to various factors including the value of their contribution to national socioeconomic development. While the patriarchal nature of African societies remains one of the major issues impacting female entrepreneurs, the Covid-19 pandemic exacerbated the situation, therefore necessitating research that addresses interventions. This study examined the challenges of female entrepreneurship before, during, and the post-Covid-19 prospects in South Africa. By examining these challenges, the study aimed to shed light on factors militating against the success of female entrepreneurship, including the Covid-19 era and proposed solutions to overcome some of the challenges. Design/methodology/approach: A descriptive literature review methodology was used to conduct this study. Findings: The findings indicate that numerous cultural, economic, and institutional factors militate against productive female entrepreneurship. In addition, the results show that while Covid-19 affected all types of firms, and female-led enterprises suffered the most. Female-owned enterprises suffered the most in terms of lost revenues, business closures, and women retreating to traditionally assigned roles as family caregivers. Research limitations/implications: Given that the pandemic resulted in some cases of business closures and scaling down operations, there is a need for targeted support efforts to resuscitate female entrepreneurs in the post-Covid-19 era. Thus, extensive government and institutional financial and non-financial support are needed for female entrepreneurs. Practical implications: The study contributes to the overall discourse on supporting women’s participation in economic activities through entrepreneurship. Originality/value: This paper is original Paper type: a Research Paper